Dietary survey in Japanese patients with type 2 diabetes and the influence of dietary carbohydrate on glycated hemoglobin: The Sleep and Food Registry in Kanagawa study. Issue 2 (31st August 2018) - Yamakawa, Tadashi; Sakamoto, Rika; Takahashi, Kenichiro; Suzuki, Jun; Matuura‐Shinoda, Minori; Takahashi, Mayumi; Shigematsu, Erina; Tanaka, Shunichi; Kaneshiro, Mizuki; Asakura, Taro; Kawata, Takehiro; Yamada, Yoshihiko; et al.
Abstract: Aims/Introduction: The present study investigated the relationship between the macronutrient energy ratio, dietary carbohydrate and glycated hemoglobin levels in Japanese patients with type 2 diabetes, to generate a potential optimal dietary intake of macronutrients for such patients. Materials and Methods: In total, 3, 032 patients participating in the Sleep and Food Registry in Kanagawa study were evaluated. Their diets were assessed for macronutrient content through a brief self‐administered dietary history questionnaire. Relevant biochemical assays were carried out. Results: The mean energy intake (±standard deviation) was 1, 711 ± 645 kcal/day. The proportion of energy supplied by protein, fat and carbohydrate were 16.3, 26.8 and 52.3%, respectively. Total fiber intake was 12.6 ± 5.7 g/day. The high glycated hemoglobin (HbA1c) group (HbA1c >8%) had significantly lower protein and higher carbohydrate intake than the low HbA1c group (HbA1c <6.5%). Higher HbA1c levels were positively correlated with unfavorable metabolic factors, including elevated body mass index and excess carbohydrate intake, and negatively correlated with age, protein intake and fiber intake. Multiple regression analysis showed a significant association between HbA1c and carbohydrate intake after adjusting for sex, age and body mass index (0.104, P  < 0.0001). Additionally, patients within the uppermost tertile for the percentage of total energy intake from carbohydrate (>60%) were most likely to have high HbA1c levels. HbA1c was significantly correlated with carbohydrate (%E) in all age groups and in patients taking one or two antidiabetic drugs. Conclusions: The dietary carbohydrate:energy ratio has a positive correlation with HbA1c, suggesting that avoiding excessive carbohydrate intake (>60%) might help foster glycemic control. Abstract : The study explored the relationship between macronutrient energy ratio, dietary carbohydrate, and glycated hemoglobin levels in selected type 2 diabetic Japanese patients. Our results indicate that dietary carbohydrate to energy ratio has a positive correlation with glycated haemoglobin.